Diseño de una Unidad de Detección del ritmo cardiaco humano para dispositivos médicos - Molina-Robles, Roberto Carlos (Instituto Tecnológico de Costa Rica, 2012)
In this report was documented the development of a cardiac rhythm Detection Unit for medic devices. With the help of the Dr. Alfonso Chacón, the M.Sc. Roberto Pereira and the Dr. Alfredo Arnaud, a base circuit capable of detecting the cardiac pulses was designed. For the solution, low-power Gm-C circuits and transistor fragmentation technics were implemented as strategies for the design. Afterwards, a computerized optimization tool was employed to improve its electrical properties. In the present document you will find all the information related to the project development, from the theoretical fundaments to the design, the tests and the results obtained in simulators.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica). Instituto Tecnológico de Costa Rica. Escuela de Ingeniería Electrónica, 2012.
Keywords: Diseño analógico; Circuitos; Circuitos Gm-C; Transitores; Pulso cardiaco; Algoritmos genéticos